Infimum problems derived from the proofs of some generalized Schwarz inequalities - Boros, Zoltán; Száz, Árpád (Teaching Mathematics and Computer Science, 2019)
We define f(a;b)(r) = ar + b/r for all a, b, r Є R with r > 0. And, for some subsets A of R, we determine FA_+ (a; b) = inf (r Є A_+) f(a,b) (r) ; where A_+ ={r Є A : r > 0}. The above in ma are mainly motivated by the proofs of some recent generalized Schwarz inequalities established by the present authors.Subject Classification: I35